Supply Chain Performance Under Market Valuation: An Operational Approach to Restore Efficiency - Lai, Guoming; Xiao, Wenqiang; Yang, Jun (Management Science, 2012)
Based on a supply chain framework, we study the stocking decision of a downstream buyer who receives private demand information and has the incentive to influence her capital market valuation. We first characterize a market equilibrium under a general, single buyback contract. We show that the buyer's stocking decision can be distorted in equilibrium. Such a downstream stocking distortion hurts the buyer firm's own performance, and it also influences the performances of the supplier and the supply chain. We further reveal scenarios where full supply chain efficiency cannot be reached under any single buyback contract. Then, focusing on contract design, we characterize conditions under which a menu of buyback contracts can prevent downstream stocking distortion and restore full efficiency in the supply chain. Our study demonstrates that in a supply chain context, a firm's incentive to undertake real economic activities to influence capital market valuation can potentially be resolved through operational means. This paper was accepted by Yossi Aviv, operations management.